Identification of serovar 1a, 1b, 2, and 5 strains of Erysipelothrix rhusiopathiae by a conventional gel-based PCR - Shiraiwa, Kazumasa; Ogawa, Yohsuke; Nishikawa, Sayaka; Eguchi, Masahiro; Shimoji, Yoshihiro (Veterinary microbiology, 2018)
•Erysipelothrix rhusiopathiae can infect both humans and a wide range of animals.•A conventional gel-based PCR assay was developed for serotyping of serovar 1a, 1b, 2, and 5 strains of E. rhusiopathiae.•The PCR assay can simultaneously detect and differentiate the disease-associated serovars.•The PCR assay is also useful for serovar surveillance of isolates in wild animals. Among the four species of the genus Erysipelothrix, Erysipelothrix rhusiopathiae is the main species that causes disease in swine and poultry and has also been isolated from human patients. Recently, E. rhusiopathiae infections in domesticated animals have increased in many countries and are also the cause of emerging wildlife disease in arctic and boreal ecosystems. Historically, E. rhusiopathiae has been differentiated from other Erysipelothrix species by their serovars, which are determined based on cell wall antigens. Serotyping of Erysipelothrix is important, as specific E. rhusiopathiae serovars (1a, 1b, and 2) are associated with disease in pigs, poultry, and humans. However, serotyping is laborious and time-consuming and requires a full set of serovar reference strains and strain-specific antiserum. In this study, to develop a conventional gel-based PCR assay that can detect the main disease-associated serovars of E. rhusiopathiae, the draft genome sequences of E. rhusiopathiae strains of serovars 1a, 1b, 2, and 5, the last of which is often isolated from wild animals, were analyzed. Primers were designed based on the serovar-specific sequences of the strains and tested for field strains isolated from extensive origins. Among two hundred and ninety-seven isolates of various serovar strains of E. rhusiopathiae and other Erysipelothrix species, the PCR assay identified serovar 1a, 1b, 2, and 5 strains of E. rhusiopathiae. This conventional gel-based PCR assay should be useful for serovar surveillance of E. rhusiopathiae isolates in domesticated and wild animals as well as in humans.